Fútbol y Tenis de Mesa: Evidencia científica de la importancia del entrenamiento visual en el rendimiento deportivo (2022)
This paper describes the most important techniques for visual training sports Visual Sports Training (EVD) in order to facilitate orientation to the optometrists who are going to be directed in the world of EVD. Additionally, it aims to show the effects found in the evidence with the application of visual therapy in athletes.